Pengembangan Media Accordion Book Pada Muatan IPA Topik Mengenal Proses Fotosintesis Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV SD - Yuandira Ragil Anggraini; Julianto Julianto; Mintohari Mintohari; Farida Istianah (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to develop an Accordion Book learning medium for science learning on the topic of photosynthesis to improve the critical thinking skills of fourth-grade elementary school students. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The subjects were fourth-grade students at SDN Canggu, who were divided into an experimental class and a control class. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest and posttest assessments. The results showed that the Accordion Book was highly valid, with material expert validation of 92.50% and media expert validation of 93.33%. The medium was also highly practical based on student responses, with percentages of 89.14% in the control class and 91.09% in the experimental class, as well as a teacher response of 94.29%. The Independent Samples T-Test yielded a significance value of < 0.001, indicating a significant difference between the learning outcomes of students in the experimental and control classes. Therefore, the Accordion Book learning medium was considered highly valid, highly practical, and effective in supporting the improvement of fourth-grade elementary school students' critical thinking skills.